Formulation development, in vitro and in vivo evaluation of chitosan engineered nanoparticles for ocular delivery of insulin. Issue 71 (8th December 2020) - Rathore, Priyanka; Mahor, Alok; Jain, Surendra; Haque, Anzarul; Kesharwani, Prashant
Abstract : Insulin-dependent diabetic patients have to count on the administration of painful and discomforting insulin injections. Abstract : Insulin-dependent diabetic patients have to count on the administration of painful and discomforting insulin injections. However, inadequate insulin absorption and the risk of insulin level escalation in the blood are some disadvantages associated with insulin therapy. Thus, the current study intends to formulate insulin-loaded chitosan nanoparticles for refining the systemic absorption of insulin via the ocular route. Insulin-loaded chitosan nanoparticles were prepared by the ionotropic gelation method and characterized for various parameters. Optimized insulin loaded nanoparticles (C4T4I4) were positively charged with a particle size of 215 ± 2.5 nm and showed 65.89 ± 4.3% entrapment efficiency. The in vitro drug release exhibited sustained release of insulin, where 77.2 ± 2.1% of release was observed after 12 h and leads to an assumption of the non-Fickian diffusion release mechanism. The permeation study discloses good mucoadhesive and better permeation properties of insulin loaded nanoparticles compared to free Insulin. No significant difference was observed in the size of particles after six months of storage, signifying their adequate stability. Nanoparticles were found to be non-irritant to ocular tissues and exhibited prominent blood glucose level reduction in vivo . The outcomes of this study suggested that the chitosan nanoparticulate system could act as a prominent carrier system for insulin with enhanced stability and efficacy.